Unconfined Compressive Strength Characteristics of Overboulder Asbuton and Zeolite Stabilized Soft Soil - Noor Dhani; Ahmad Gasruddin; Hartini Hartini; La Baride (Salehan Institute of Higher Education, 2021)
Soft soil was one of the most widely encountered problems in construction, especially for archipelago countries which most of its area was lowland with a high deposit of soft soil. To overcome this problem, soil stabilization was one of the most widely used as a solution. Soil stabilization in general uses chemical substances that are classified as pozzolan material. Pozzolan material uses its capability to strengthen the cohesion of soil grains. Mostly, pozzolan material consists of silica. Overboulder asbuton and zeolite were examples of natural pozzolan material in Indonesia. Both materials have a high silica content. Thus, the author interested to figure out the mechanical behavior of these two substances as a soil stabilizer. This research was a correlating study to the previous paper with the same author which discusses the overboulder asbuton as a soil stabilizer. Overboulder added to the mix is determined as 15%, with varied zeolite percentages applied to examine the differences. The UCT was conducted according to ASTM D-2166 as a parameter. As the standard remolding method, a standard proctor test was conducted to determine the optimum moisture content and the maximum density of each mix. While the UCT specimens were tested at the certain curing time for each composition. The curing time applied was 0, 7, 14, and 28 days. By this curing period, the effective pozzolanic reaction that occurs for each composition could be determined. The result shows that zeolite addition to overboulder asbuton could increase the soil density and increase its compressive strength. It is indicated that overboulder asbuton and zeolite mix could be a proper alternative as a soil stabilizer. Doi: 10.28991/cej-2021-03091635 Full Text: PDF